Cardio-Nephroprotective Effects of Guava and Olive Leaves Extracts on Doxorubicin-Induced Toxicity in Rats - Eman Aly Sadeek Fadlalla (Journal of Pharmacy and Nutrition Sciences, 2018)
Objective: Doxorubicin (DOX) is an anticancer drug that is known to increase oxidative stress in several organs. Our objective was to evaluate the possible cardioprotective and nephroprotective effects of guava leaves extract (GLE) and olive leaves extract (OLE) on DOX-induced toxicity in rats. Methods: Forty adult male albino rats were randomly divided into 4 groups of 10 rats each, as follows: a normal control group, a DOX group (a single dose of DOX; 30 mg/kg intraperitoneally), a GLE group (500 mg GLE/kg body weight), and an OLE group (500 mg OLE/kg body weight) for 12 d. DOX was administered in the DOX, GLE, and OLE rats, which were sacrificed 4 d after DOX administration. Results: DOX injection resulted in a significant elevation in serum lactate dehydrogenase, creatinin kinase-MB (CK-MB), total protein, urea, and creatinine. Cardiac as well as renal glutathione (GSH) and catalase (CAT) were significantly decreased, whereas tissue lipid peroxidation significantly increased. Pretreatment with GLE and OLE significantly reduced the elevated concentrations of serum lactate dehydrogenase, KC- MB, urea, creatinine and total protein (P < 0.05). GLE and OLE increased cardiac as well as renal GSH and CAT concentrations and decreased malondialdehyde concentrations. Conclusions: GLE and OLE showed promising protective effects against DOX-induced cardio-nephrotoxicity, which might be attributed to their antioxidant activities.